Filsafat Harapan Ernst Bloch: Dimensi Sosial dan Politik dari Harapan - Robertus Wijanarko (Sekolah Tinggi Widya Sasana, 2021)
Hope is an important theme to reflect on, especially at the time of covid-19 pandemic. This study explores Ernst Bloch’s philosophy of hope. I utilize critical analysis method to investigate Bloch’s work, The Principle of Hope, which then is supported by other secondary resources concentrated on Bloch’ thoughts. I organize this study into several sections. After giving a short introduction, I illustrate his short biography that shaped the development of his thoughts. In the following section, I systematically explore his basic ideas on hope, and then try to synthesize his thoughts under title “Social and Political Dimension of Hope.” At the end I exhibit the implication and contribution of Bloch’s ideas to our situation today. The point that I found in this study is that hope is rooted in human drives for self-preservation, and carries social and political dimensions. Since this is only preliminary study, I found some difficulties in finding Indonesian terms to articulate Bloch’s thoughts.